Pedagogical Tools in EFL Learning: Using YouTube Videos to Improve the Learners’ Ability to Perform their Speaking Skill - Fazilet ALACHAHER; Latifa CHKHI; Fatima Zohra ENNEBATI (Langues & Cultures)
The pedagogical use of the YouTube platform raised many questions to discuss the efficiency of learning a foreign language. The content that the YouTube platform may offer includes many programs for the use of English performing learners’ independent learning especially in practicing his/her speaking skill. This is considered as a starting point towards individual performance where serious attention is paid to learn via a self-directed method following the range of language teachers. The study aims at finding out whether or not or now not; students of English at Tlemcen University who are geared up to apply YouTube for a particular objective. In addition, this study attempts to bring some new advantages to the English learning field of study and research.